Distractions and Defractions: Using Parental Rights to Fight Against the Educational Rights of Transgender, Nonbinary, and Gender Diverse Students. Issue 2 (March 2021) - Mayo, Cris
In recent years, conservative advocates have obscured their transphobia by framing their concerns as religiously-based parental rights claims. They have advocated for limitations on youth rights to gender identity self-determination. This article examines policy debates over transgender-inclusive practices in schools, including conservative demands for parental notification and limitations on healthcare access for transgender youth. I suggest that schools ought to be more concerned with children's or students' rights to help enable diverse students to flourish and become who they are in supportive schools. This shift would move schools away from the distractions of conservative parental rights claims and re-focus them instead on the needs of students.